MENGURAI ENDEMISITAS DBD DI PROVINSI NTB MELALUI DETERMINASI SOSIAL DAN LINGKUNGAN: SEBUAH KAJIAN EPIDEMIOLOGI - Lalu Herman Mahaputra; Anna Indriani; Sadikin Apriadi; Elya Endriani; Susi Wirawati Triono; Yuly Peristiowati (Bajang Institute, 2025)
Objective: This article aims to unravel the endemicity of Dengue Hemorrhagic Fever (DHF) in West Nusa Tenggara Province through an analysis of social and environmental determinants from an epidemiological perspective. This study seeks to provide a comprehensive understanding of the factors that maintain the dengue transmission cycle in the region. Methods: This study used a narrative literature review approach, searching publications from Google Scholar, PubMed, ScienceDirect, DOAJ, and official reports such as the NTB Health Profile, Ministry of Health DHF surveillance data, and Riskesdas. Literature was selected based on its relevance to the topic of DHF endemicity, social, environmental, behavioral, and vector dynamics determinants. The analysis was conducted using narrative synthesis using an environment-based disease epidemiology approach and the Social Determinants of Health framework. Results: The study results indicate that DHF endemicity in NTB is influenced by the interaction of social, environmental, and behavioral factors. Poor sanitation conditions, household water storage practices, population density, low 3M+ PSN behavior, and limited health literacy are the dominant factors. Furthermore, seasonal rainfall, climate change, and inequitable health services contribute to the continued cycle of transmission. Urban areas such as Mataram City and West Lombok have a higher incidence due to population density and mobility. Implications: Efforts to control dengue fever endemicity in West Nusa Tenggara (NTB) require an integrated, multisectoral approach, including strengthening environmental management, community-based mosquito breeding sites, health education, improving water and sanitation infrastructure, and strengthening epidemiological surveillance systems. Limitations: As a literature review study, this research relies on the availability and completeness of secondary data. Variations in data between sources can affect the consistency of interpretation, and no quantitative statistical analysis was performed to measure the strength of the relationship between variables.